2016
DOI: 10.3851/imp3131
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sofosbuvir Resistance-Associated Variants in Brazilian and Worldwide NS5B Sequences of Genotype-1 HCV

Abstract: Resistant variants to sofosbuvir were found at different frequencies in worldwide HCV-1b sequences but not in HCV-1a sequences. The high frequency of double mutation L159F-C316N observed in Brazilian HCV-1b patients contrast with the lower rate observed in the three continents studied. The association of these findings and the clinical implications awaits further analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…Previous studies have found variable prevalence of C316N in Brazil, from 3.85% (Peres-da-Silva et al, 2017) to 11.6% (Castillho et al, 2011), 16.3% (Noble et al, 2017), and 24% (Castilho et al, 2011), and higher prevalence in North America (16.81%), Europe (7.47%), and Asia (49.71%) (Peres-da-Silva et al, 2017). The higher prevalence of mutations in genotype 1b has been reported previously and it was due to the presence of C316N (Paolucci et al, 2013;Peres-da-Silva et al, 2017).…”
Section: Resultssupporting
confidence: 57%
“…Previous studies have found variable prevalence of C316N in Brazil, from 3.85% (Peres-da-Silva et al, 2017) to 11.6% (Castillho et al, 2011), 16.3% (Noble et al, 2017), and 24% (Castilho et al, 2011), and higher prevalence in North America (16.81%), Europe (7.47%), and Asia (49.71%) (Peres-da-Silva et al, 2017). The higher prevalence of mutations in genotype 1b has been reported previously and it was due to the presence of C316N (Paolucci et al, 2013;Peres-da-Silva et al, 2017).…”
Section: Resultssupporting
confidence: 57%
“…L159F is not associated with reduced sofosbuvir susceptibility, although this RAS was frequently detected with C316N. The high frequency of this double mutation was reported in untreated Brazilian patients infected with GT1b 53. The combination of L159F with C316N was also frequently found in GT1b-infected patients who failed to respond to sofosbuvir/ribvirin or other sofosbuvir-based regimens 54.…”
Section: Discussionmentioning
confidence: 96%
“…(2017) [33] and Peres-da-Silva A. et al . (2017) [15] whose prevalence was 14.2% (8/56) and 25% (13/52), respectively. The occurrence of these RASs did not appear to have influenced therapeutic response after treatment, since all HCV GT 1b-monoinfected patients has achieved SVR.…”
Section: Discussionmentioning
confidence: 99%